1987
DOI: 10.1016/0301-9322(87)90046-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of particle-laden turbulent water jets in still water

Abstract: Abstract--The structure of turbulent, dilute, particle-laden water jets, submerged in still water, was studied both experimentally and theoretically. Nonintrusive measurements were made of mean and fluctuating phase velocities and particle number fluxes. Analysis was used to help interpret the measurements, considering three limiting cases, as follows: (1) locally-homogeneous flow, where relative velocities between the phases are ignored; (2) deterministic separated flow, where relative velocities are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 21 publications
8
28
0
Order By: Relevance
“…For the constants involved in the K-ε model, Squires and Eaton [64] concluded that for dilute flows with mass loadings below 0.2, the modification in the values of the constants are small (although some caution should be taken in cases of preferential concentration of particles). Therefore, we have used the unmodified values of the constants in the turbulence models, following customary approaches in most papers (see, for instance, [2,14,23,32,55,73]). In the case of the K-ω model, [43,74] have used the same constants that were suggested by Wilcox [72].…”
Section: Considerations About the Values Of The Model Constantsmentioning
confidence: 99%
“…For the constants involved in the K-ε model, Squires and Eaton [64] concluded that for dilute flows with mass loadings below 0.2, the modification in the values of the constants are small (although some caution should be taken in cases of preferential concentration of particles). Therefore, we have used the unmodified values of the constants in the turbulence models, following customary approaches in most papers (see, for instance, [2,14,23,32,55,73]). In the case of the K-ω model, [43,74] have used the same constants that were suggested by Wilcox [72].…”
Section: Considerations About the Values Of The Model Constantsmentioning
confidence: 99%
“…Ferrante and Elghobashi [10] analyzed the mechanism of particle modification of low-wavenumber energy transfer. In experimental studies on jet two-phase turbulence, large particles enhanced gas-phase turbulence intensity, while small particles attenuated turbulence intensity [2,[11][12][13][14][15]. The two-phase inter-phase interaction in a turbulent channel flow laden with heavy particles has not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Large particles can augment turbulence intensity due to unsteady particle wakes or the superposition of many randomly positioned laminar or laminar-like wakes [2][3][4]. However, extra dissipation of turbulence by particles can cause turbulence attenuation.…”
Section: Introductionmentioning
confidence: 98%
“…Brush (1962) investigated the spreading rate of the velocity of the solid phase and fluid phase in the vertically downward jet as a function of particle size which was also obtained from photographic measurements of sand jets by Mazurek et al (2002). The velocity and turbulence characteristics of a vertically downward jet of glass spheres and water were studied by Parthasarathy and Faeth (1987), with initial particle concentrations up to 4.8%, using a laser Doppler anemometer. Jiang et al (2005) measured the velocities of both lower-density fluorescent hollow glass beads and polyamide particles as a two-phase vertically downward jet through particle image velocimetry, and theoretically derived an equation for vertically upward jet that compared well with experimental measurements for a ground deposit made by Neves and Fernando (1995).…”
Section: Introductionmentioning
confidence: 99%